Auxin reflux between the endodermis and pericycle promotes lateral root initiation. (23rd November 2012) - Marhavý, Peter; Vanstraelen, Marleen; De Rybel, Bert; Zhaojun, Ding; Bennett, Malcolm J; Beeckman, Tom; Benková, Eva
Abstract : Lateral root (LR) formation is initiated when pericycle cells accumulate auxin, thereby acquiring founder cell (FC) status and triggering asymmetric cell divisions, giving rise to a new primordium. How this auxin maximum in pericycle cells builds up and remains focused is not understood. We report that the endodermis plays an active role in the regulation of auxin accumulation and is instructive for FCs to progress during the LR initiation (LRI) phase. We describe the functional importance of a PIN3 (PIN‐formed) auxin efflux carrier‐dependent hormone reflux pathway between overlaying endodermal and pericycle FCs. Disrupting this reflux pathway causes dramatic defects in the progress of FCs towards the next initiation phase. Our data identify an unexpected regulatory function for the endodermis in LRI as part of the fine‐tuning mechanism that appears to act as a check point in LR organogenesis after FCs are specified. Auxin reflux between the endodermis and pericycle promotes lateral root initiation: The auxin efflux carrier PIN3 regulates auxin transport from the endoderm to pericycle founder cells to promote lateral root formation in Arabidopsis .